2016
DOI: 10.1007/s13197-016-2241-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of molecular weight distribution of unreduced wheat gluten proteins associated with noodle quality

Abstract: Unreduced gluten proteins of Indian wheat varieties viz.C306, DBW16, HI977 and HW2004 were separated using size-exclusion chromatography (SEC). Statistical correlation of area % of eluted peaks with properties of flour, dough and noodles was elucidated. Chromatograms of gluten proteins were classified primarily into five peaks in decreasing molecular size range and relative proportion were expressed in terms of area % of individual peaks which depicts the quantitative variation in protein eluted at different r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Chaudhary, Dangi, and Khatkar (2016a) assessed gluten protein molecular weight distribution and its association with chapatti quality, and determined that dough properties are positively impacted by glutenins, whereas gliadins show a negative association. Chaudhary, Dangi, and Khatkar (2016b) investigated noodle quality in the same manner and found that glutenin polymeric proteins show a positive correlation with cooking time and cooked weight, whereas gliadins show a negative correlation. In the present study, glutenin polymeric proteins showed a positive correlation with dough quality and baking quality, which is in line with the findings of Ohm et al (2010) and Chaudhary et al (2016c).…”
Section: Protein Size-exclusion Hplc and Quality Characteristicsmentioning
confidence: 99%
“…Chaudhary, Dangi, and Khatkar (2016a) assessed gluten protein molecular weight distribution and its association with chapatti quality, and determined that dough properties are positively impacted by glutenins, whereas gliadins show a negative association. Chaudhary, Dangi, and Khatkar (2016b) investigated noodle quality in the same manner and found that glutenin polymeric proteins show a positive correlation with cooking time and cooked weight, whereas gliadins show a negative correlation. In the present study, glutenin polymeric proteins showed a positive correlation with dough quality and baking quality, which is in line with the findings of Ohm et al (2010) and Chaudhary et al (2016c).…”
Section: Protein Size-exclusion Hplc and Quality Characteristicsmentioning
confidence: 99%
“…While a similar pattern was observed in HI1500, but the values were significantly higher due to the varietal and basic compositional difference in gluten composition. Chaudhary et al (2016b) findings imply that polymeric proteins network with starch polymer slows the hydration of noodles by reducing the amount of water available during cooking and lengthening the cooking time. Furthermore, the water diffusion ability during the rehydration and cooking process is influenced by noodle porosity offering the framework for water to infiltrate into the middle of the noodles (Jang, Kim, & Lee, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Fractionation of wheat gluten proteins by SEC SEC fractionated unreduced gluten proteins into five peaks, namely, peak I, II, III, IV and V in order of decreasing molecular size of eluted proteins (Chaudhary et al 2016b). Protein fraction eluted in peak I at 68.00-89.07 min was enriched in polymeric glutenin proteins i.e.…”
Section: Resultsmentioning
confidence: 99%